Polarisation of polar dumbbell fluids in thermal gradients: the importance of the treatment of electrostatic interactions. (16th November 2016) - Daub, Christopher David; Åstrand, Per-Olof; Bresme, Fernando
ABSTRACT: We use non-equilibrium molecular dynamics simulations to study dipolar dumbbell fluids in a thermal gradient. We study the relative orientation of size asymmetric molecules with respect to the thermal gradient, and the sensitivity of the orientation to whether the Wolf method or Ewald summation is employed to compute the electrostatic interactions. For these systems, we find that the Wolf method overestimates the degree of molecular orientation. We also present new data on fluids with very small dipole moments which give novel insight into how the molecular asymmetry influences the polarisation response in the thermal gradient. Abstract :